Analisis Resiko Kecelakaan Kerja pada Proses Operasional PT Pelindo Multi Terminal Menggunakan Metode Hazop - Rizky Sanjaya Nainggolan; Saina Tesalonika Br Perangin Angin; Anita Christine Sembiring (Jurnal Rekayasa Proses dan Industri Terapan, 2025)
The biomass-fueled Steam Power Plant (PLTU) at PT Pelindo Multi Terminal presents a relatively high potential risk of occupational accidents due to the use of flammable fuel, extreme pressure and temperature conditions, and the complexity of operational equipment. This study aims to identify potential hazards, assess risk levels, and provide mitigation recommendations using the Hazard and Operability Study (HAZOP) method. Data were collected through field observations, interviews with workers and supervisors, as well as a review of operational documents and accident reports. The analysis revealed several major risks, including fire, explosion, steam leakage, exposure to toxic gases, and accidents caused by equipment failure. Risk assessment using the HAZOP matrix identified several critical points, particularly during the biomass combustion process, high-pressure steam treatment, and turbine operation. The risk levels ranged from moderate to high, requiring planned and systematic mitigation measures. Recommended strategies include strengthening temperature and pressure control systems, implementing regular maintenance and inspection of equipment, ensuring proper provision and use of personal protective equipment (PPE), enhancing worker capacity through occupational safety training, and installing early detection systems for fire and gas leaks. The implementation of these recommendations is expected to minimize workplace accidents, improve worker safety awareness, and support the creation of a safer, more efficient, and sustainable working environment in the operation of the biomass steam power plant.